Shoulder Impairment Following Critical Illness: A Prospective Cohort Study. Issue 11 (November 2018) - Gustafson, Owen D.; Rowland, Matthew J.; Watkinson, Peter J.; McKechnie, Stuart; Igo, Simon
Abstract : Objectives: Identify the prevalence of shoulder impairment in ICU survivors within 6 months of discharge from ICU. Evaluate the impact of shoulder impairment on upper limb functional status in patients treated on an ICU. Identify risk factors for the development of shoulder impairment. Design: Prospective cohort study. Setting: A tertiary care medical-surgical-trauma ICU at a U.K. hospital over 18 months, with a further 6-month follow-up after hospital discharge. Subjects: Adult patients with an ICU length of stay of greater than 72 hours with no preexisting or new neurologic or traumatic upper limb injury. Interventions: None. Measurements and Main Results: Patients underwent targeted shoulder assessments (pain, range of movement, Constant-Murley Score, shortened version of the disabilities of the arm, shoulder, and hand [DASH] score [QuickDASH] score) at hospital discharge, 3 and 6 months after hospital discharge. Assessments were undertaken on 96 patients, with 62 patients attending follow-up at 3 months and 61 patients at 6 months. Multivariate regression analysis was used to investigate risk factors for shoulder impairment. ICU-related shoulder impairment was present in 67% of patients at 6 months following discharge from hospital. Upper limb dysfunction occurred in 46%, with 16% having severe dysfunction (equivalent to shoulder dislocation). We were unable to identify specific risk factors for shoulder impairment. Conclusions: Shoulder impairment is a highly prevalent potential source of disability in ICU survivors. This persists at 6 months after discharge with a significant impact on upper limb function. More research is needed into potential mechanisms underlying shoulder impairment and potential targeted interventions to reduce the prevalence. Abstract : Supplemental Digital Content is available in the text.